Data acquisition time minimization in FANET-based IoT networks - Albu-Salih, Alaa Taima; Khudhair, Hayder Ayad; Hilal, Osama Majeed (Kuwait Journal of Science, 2021)
Unmanned aerial vehicles (UAVs) is widely used in many military, and civilian applications. UAVs communicate in a Flying Ad hoc Network (FANET) environment where UAVs communicate with each other through an ad hoc network without infrastructure. FANET provide a flexible platform for internet of things (IoT) applications by playing different roles in IoT such as mobile data collector. In fact, in deadline-based IoT applications, the deadline is restricted to the critical application level, and as a result, this deadline for data acquisition is not adequate, and FANET cannot collect data from the sensed area with predetermined deadline. In this paper, a novel efficient data gathering approach for IoT using FANET is proposed. The main objective of this approach is to solve the problem of insufficient deadlines given by FANET in IoT-based deadline applications. We will first provide a multi-objective optimization model as a MILP optimization model to solve this problem, and then normalize and add two weighing coefficients to solve the MILP model. The results obtained in the simulation show that the proposed approach is able to provide efficient data acquisition while guaranteeing the deadline time.